Debt management in a world of fiscal dominance - Boris Chafwehé; Charles De Beauffort; Rigas Oikonomou (European Commission, Joint Research Centre (JRC), 2021)
We study the impact of debt maturity management in an economy where monetary policy is 'passive' and subservient to fiscal policy. We setup a tractable model, to characterize analytically the dynamics of in ation, as well as other macroeconomic variables, showing their dependence on the monetary policy rule and on the maturity of debt. Debt maturity becomes a key variable when the monetary authority reacts to in ation and the appropriate maturity of debt can restore the efficacy of monetary policy in controlling in ation. This requires debt management to focus on issuing long bonds. Moreover, we propose a novel framework of Ramsey optimal coordinated debt and monetary policies, to derive analytically the interest rate rule followed by the monetary authority as a function of debt maturity. The optimal policy model leads to the same prescription, long term debt financing enables to stabilize in ation. Lastly, the relevance of debt maturity in reducing in ation variability is also confirmed in a medium scale DSGE model estimated with US data.
Keywords: E31; E52; E58; E62; C11; 330; Passive Monetary Policy; Government Debt Management; Fiscal and MonetaryPolicy Interactions; Bayesian estimation; Ramsey policy